New Empirical Findings about the Interaction between Public Employment Agency and Private Search Effort - Christian Holzner; Makoto Watanabe (Center for Economic Studies and ifo Institute (CESifo), 2024)
The Public Employment Agency (PEA) helps unemployed to find work and mediates PEA-registered job vacancies to job seekers via vacancy referrals. Using the spatial and temporal variation resulting from the regional roll-out of the Hartz 3 reform we are able to show that Hartz 3, which changed the counseling process of unemployed, decreased the fraction of unemployed that received vacancy referrals, increased the job-finding probability of unemployed without vacancy referrals, left the job-finding probability of unemployed with vacancy referrals unaffected, and increased average wages of newly hired, previously unemployed. Since the existing literature is not able to explain this set of findings, we develop a simple theoretical directed search model, which does. It does so by considering the interaction between the private market and the intermediation provided by the PEA.
Keywords: J08; J30; J60; 330; public employment agency; natural experiment; job-finding probability; wages